Photo Essay - Imreh, L. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1978)
Summary This photo-essay presents a few pictures showing some of the features of meta-ultramafic komatiitic submarine flows of Archean age from the spectacular La Motte - Vassan ultramafic belt, situated northwest of Val d'Or in northwest Quebec. The writer has spent the past five field seasons ( 1972-1977) in this region and the volcano-sedimentary foreland in Abitibi-est, Temiscaningue and Rouyn-Noranda counties. The material shown here is part of a larger publication (Imreh. 1978) produced by the Québec Ministère des Richesses naturelles. Spinifex textures are shown in Figures 1 and 2: microspinifex in Figure 4 and (at a larger scale) Figure 5. Not all flows show spinifex: Figure 3 shows the contact between two flows without spinifex. Micro-spinifex in pockets within massive flows, as shown in Figures 4 and 5. is always limited to the upper parts of flows without spinifex zones Details of spinifex textures, as well as mega-pillow structure (Figure 6) can be used to indicate the tops of the flows